2013
DOI: 10.1007/s10745-013-9564-1
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Perspectives on Shifting Cultivation Landscapes in Northern Laos

Abstract: Abstract:Despite the rapid agricultural transition which has occurred in the past decade, shifting cultivation remains a widespread agricultural practice in the northern uplands of Lao PDR. Little information is available on the basic socio-economic situation and respective possible patterns in shifting cultivation landscapes on regional level. Based on a recent approximation of the extend of shifting cultivation landscapes for two time periods and disaggregated village level Census data, this papers character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…However, in the last decade, villagers in general in many parts of the world have started to change their farming methods from shifting to permanent cultivation (Hariyadi and Ticktin 2012;Heinimann et al 2013;Mertz 2009). In Expansion of traditional land-use and deforestation: a case study of an adat forest in the… 497 response to better access to urban areas and changing prices, many farmers have started to cultivate permanent rubber or oil palm crops mixed with upland rice.…”
Section: Research Areamentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the last decade, villagers in general in many parts of the world have started to change their farming methods from shifting to permanent cultivation (Hariyadi and Ticktin 2012;Heinimann et al 2013;Mertz 2009). In Expansion of traditional land-use and deforestation: a case study of an adat forest in the… 497 response to better access to urban areas and changing prices, many farmers have started to cultivate permanent rubber or oil palm crops mixed with upland rice.…”
Section: Research Areamentioning
confidence: 99%
“…Following the introduction of Forestry Law No. 41/1999, concerning the change in status from adat forest to state forest, adat communities living in these forests, who have done so for generations, have been accused of encroaching (Hartanto et al 2008). In many parts of Indonesia, adat communities have been blamed for deforestation and forest destruction (Cahyadi 2014;IWGIA 2011;Wijaya 2014).…”
mentioning
confidence: 99%
“…Human effort to tap forest resources for life necessities ends up destroying the natural ecosystem influencing forest carbon stock [27]. Research findings showed that forest contributes about 22%…”
Section: Livelihood Economic Activitiesmentioning
confidence: 99%
“…In spite of such a situation of deforestation and its drivers, shifting cultivation has been dominant land use system in the northern Lao PDR, securing the livelihoods of the large percentage of the rural population living in mountainous area (Heinimann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%